2021
DOI: 10.21037/atm-20-5419
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of chimeric antigen receptor-T (CAR-T) cell therapy for lung cancer

Abstract: Lung cancer represents one of the most common and deadliest cancers in the world. Chimeric antigen receptor-T cell (CAR-T) therapy which can recognize antigens in a major histocompatibility complex (MHC)-independent manner provides a new approach for tumor treatment. However, lung cancer, as a solid tumor, faces several formidable barriers to adoptive cell transfer, which includes inhibition of T-cell localization and suppression of T-cell function. Therefore, lung cancer fails to respond significantly to infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…CEACAM5, a glycosylated transmembrane protein, is often presented in lung cancer tumor tissues (42). CEACAM5-targeted therapies, including CAR-T cells (43) or ADCs (20), have been developed against lung cancer. Here, we investigated the efficacy of such therapeutic modalities targeting CEACAM5 in ADC-sensitive and -resistant NSCLC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…CEACAM5, a glycosylated transmembrane protein, is often presented in lung cancer tumor tissues (42). CEACAM5-targeted therapies, including CAR-T cells (43) or ADCs (20), have been developed against lung cancer. Here, we investigated the efficacy of such therapeutic modalities targeting CEACAM5 in ADC-sensitive and -resistant NSCLC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…However, the published literature of the therapeutic effect of CAR T-cells in solid tumors shows their efficacy is unfortunately impeded by T cell homing and infiltration into the tumor ( 13 ). Regional delivery of CAR T-cells, such as intrapleural, intracranial, and intraperitoneal administration has demonstrated superior antitumor response and safety compared to systemic administration ( 14 - 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple CAR-T cell products were approved by the Food and Drug Administration (FDA) by the year 2022 [ 11 , 12 , 13 ]. Their use in solid tumor research is still ongoing [ 14 ], but many preclinical studies have demonstrated superior efficacy in the treatment of solid tumor models, including glioblastoma [ 15 ], sarcoma [ 16 ], neuroblastoma [ 17 ], breast cancer [ 18 ], advanced gastric or pancreatic cancer [ 19 ], lung cancer [ 20 ], hepatocellular carcinoma [ 21 ], ovarian cancer [ 22 ], and prostate cancer [ 23 ]. Clinical trials of CAR-T therapy targeting mesothelin (MSLN) [ 24 ], epidermal growth factor receptor (EGFR) [ 25 ], human epidermal growth factor receptor 2 (HER2) [ 26 ], and carcinoembryonic antigen (CEA) [ 27 ] in NSCLC have been completed in recent years, but with disappointing results.…”
Section: Introductionmentioning
confidence: 99%